Stability analysis on gas-lubricated bearing for high speed cryogenic turbo-expander. Issue 1 (1st May 2022) - Zheng, L W; Zhang, X H; Peng, N; Yan, H; Ke, C L; Li, K R; Liang, Y W; Xiong, L Y; Dong, B; Li, J; Liu, I Q
Abstract: Here, instead of using static characteristics of gas journal bearing such as the damping coefficients and the misalignment angle for stability analysis, a linear method is presented for studying the whirl stability of a rigid rotor supported on both cylindrical bearing and externally pressurized bearing. First, by using linearization method, the gas film forces can be represented as 8-coefficents, and they are calculated through perturbation method, the static performance is validated by published literature. Then, based on the Routh-Hurwitz criterion, the stability threshold is determined and graphically presented regarding several non-dimensional system parameters, which reflects the effects of both the eccentricity and supply pressure on the system's linear stability. This effective and computationally cheap method of stability analysis is helpful for the prior design of gas bearing.